Safety and efficacy of a feed additive consisting of potassium ferrocyanide for all animal species (K + S KALI GmbH)* - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2023)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of potassium ferrocyanide as a technological feed additive, functional group anticaking agents, for all animal species. The additive potassium ferrocyanide is intended to be used in potassium chloride with a maximum content of 150 mg ferrocyanide anion/kg salt. The use of potassium ferrocyanide is safe, when added to potassium chloride at a maximum content of 150 mg ferrocyanide anions (anhydrous)/kg for: pigs for fattening and lactating sows, sheep, goats, salmon and dogs. In the absence of a margin of safety, the use of potassium chloride according to the proposed conditions of use is not considered to be safe for chickens for fattening, laying hens, turkeys, piglets, veal calf, cattle for fattening, dairy cows, horse, rabbit and cats. In the absence of information on the use of potassium chloride in the diets for any other animal species, no conclusion on a potentially safe level of potassium chloride, supplemented with 150 mg ferrocyanide/kg, can be made. The use of potassium ferrocyanide in animal nutrition is of no concern for consumer safety. The results of in vivo studies showed that potassium ferrocyanide is not irritant to skin and eye and is not a skin sensitiser. However, due to the presence of nickel, the additive should be considered as a respiratory and dermal sensitiser. The available data do not allow the FEEDAP Panel to conclude on the safety of the additive for the soil and the marine environment, while the use of the additive in land‐based aquaculture according to the proposed conditions of use is considered of no concern. Potassium ferrocyanide is considered to be efficacious as an anticaking agent when included in potassium chloride at the proposed use levels.